The Effects of the Foster care Contract for the Algerian Foster child on French Territory - Chammam, Mounir (Journal of Legal Studies and Researches, 2021)
The Algerian legislator has given the effect of the kafala contract a specific legal framework, This changes the status of the abandoned child to a legal status of the makfol child Under the tutelage of a kafile who will protect him. The French Minister of Justice to clarify the situation of the children Under The kafala in order to relieve the constant pressure on the French administration. In this paper, we compare the kafala to the tutelage and to the delegation of parental authority taken in French civil law